Politik Identitas pada Pemilihan Kepala Desa di Desa Dolog Huluan Kecamatan Dolog Masagal Kabupaten Simalungun - Berutu, Rini Armianti; Saragih, Asha Yatri; Gurning, Fretty Luciana; Pasaribu, Anjelina; Halking, Halking (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to find out how Identity Politics in the Village Head Election in Dolog Huluan Village, Dolog Masagal District, Simalungun Regency. The research method in this study is qualitative descriptive research. Data was collected through direct interviews with resource persons who were the subjects of the research, field observations, and documentation. Data analysis is carried out using data reduction, data presentation, and data verification. The results of the study show that identity politics is carried out based on clans because the village has 4 clans that are very thick, namely the Simalungun clan consisting of SISADAPUR, namely Sinaga, Saragih, Damanik, Purba. This makes people feel that because it means a family. This is one of the causes of identity politics in the Village Head Election in Dolog Huluan Village, Dolog Masagal District, Simalungun Regency